INOVASI PENDIDIKAN GURU KEJURUAN TEKNIK MESIN - Endroyo, Bambang; Ramelan, Ramelan (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Negeri Semarang, 2005)
Development in vocational education should be in effort so that the graduates could fulfill the demand especially in industrial market. As the consequences, vocational education needs competent teachers. One of the teaching educations is mechanical engieeri ng vocational teaching school. Due to development in technology, communitys needs, philosophy of vocational education, education management and admin istration, and new regulation, inovation absolutely should be done. It means that realistic prediction should be done based on current data to determine future steps. The innovations the writer proposes are: (I) diversification on studies, (2) unity in administering vocational teaching education, (3) redefining vocational teachers com petency, and (4) orientation to vocational school teachers for internationalvocational schools.